Effect of Cross‐Linked Structures on Mechanical Properties of Styrene‐Butadiene Rubber via Molecular Dynamics Simulation. Issue 2 (12th October 2021) - Zhang, Jing; Wang, Wei; Wang, Yinbin; Qiu, Chenglong; Mao, Chengli; Deng, Shengwei; Wang, Jian‐guo
Abstract: Styrene‐butadiene rubber (SBR) is currently the main material for manufacturing passenger car tire treads due to excellent mechanical properties. The SBR is usually subjected to vulcanization treatment to improve the performance. This work uses molecular dynamics simulation to study the uniaxial stretching process of SBR with different cross‐linking degrees, and analyzes the relationship between its molecular chain structures and mechanical properties. The results show that the cross‐linked SBR model begins to deform plastically when the strain reaches 2.2, and there is no overall breaking within the limited deformation (≤4). Instead, it presents the characteristics of continuous partial breaking. Through the energy analysis, the deformation of the SBR system is mainly to overcome the energy required for the transformation of the non‐oriented chain structure to the straight chain structure and the continuous stretching of the chain. In the cross‐linked system, the increase in bond energy and bond angle energy associated with cross‐linking dramatically increases the total energy of the system, thereby affecting the overall mechanical properties. In addition, temperature and strain rate have significant effects on the tensile properties of the cross‐linked SBR system. Especially, the increase in the cross‐linking degree reduces the temperature dependence of its stress‐strain behavior. Abstract : The molecular dynamics simulation is used to study the mechanical behavior of styrene butadiene rubber with different cross‐linking degrees, and the structure‐property relationship between molecular chain structure and mechanical properties is established. The effects of temperature, strain rate and cross‐linking degree are mainly investigated, which provides theoretical guidance for the prediction of the mechanical properties of vulcanized styrene butadiene rubber.